Hum and Otoacoustic Emissions May Arise Out of the Same Mechanisms - Frosch, Franz Günter (Journal of Scientific Exploration, 2014)
Hum, a low-frequency subjective tone, affects approximately 2% of the population. Spontaneous otoacoustic emissions are sounds emitted from the inner ear, which in some cases are also perceived as tinnitus. The mechanisms of their generation, however, are still not well understood. In this paper, it is demonstrated that many properties reported by hum-sufferers (derived from both questionnaires and my own measurements) are also found in spontaneous otoacoustic emissions. The similarities of such responses suggest that both phenomena may be formed by the same mechanism. A hearing model is proposed that overcomes the limitations of the current models and explains the occurrences of spontaneous otoacoustic emissions and hum. Keywords: Hum-otoacoustic emission-Van der Pol-oscillator-hearing model-tinnitus